Alcohol-assisted rapid growth of vertically aligned carbon nanotube arrays. (September 2015) - Li, Yang; Xu, Geng; Zhang, Hao; Li, Taotao; Yao, Yagang; Li, Qingwen; Dai, Zhendong
Abstract: Millimeter-to-centimeter scale vertically aligned carbon nanotube (VACNT) arrays are widely studied because of their immense potential in a range of applications. Catalyst control during chemical vapor deposition (CVD) is key to maintain the sustained growth of VACNT arrays. Herein, we achieved ultrafast growth of VACNT arrays using Fe/Al2 O3 catalysts by ethanol-assisted two-zone CVD. One zone was set at temperatures above 850 °C to pyrolyze the carbon source and the other zone was set at 760 °C for VACNT deposition. By tuning synthesis parameters, up to 7 mm long VACNT arrays could be grown within 45 min, with a maximal growth rate of ∼280 μm/min. Our study indicates that the introduction of alcohol vapor and separation of growth zones from the carbon decomposition zone help reduce catalyst particle deactivation and accelerate the carbon source pyrolysis, leading to the promotion of VACNT array growth. We also observed that the catalyst film thickness did not significantly affect the CNT growth rate and microstructures under the conditions of our study. Additionally, the ultralong CNTs showed better processability with less structural deformation when exposed to solvent and polymer solutions. Our results demonstrate significant progress towards commercial production and application of VACNT arrays.